(untitled) (Palapa: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2022)
The problem that is the subject of this research is the low student learning outcomes, learning has not been varied and the jigsaw method has never been applied in the classroom. The purpose of this study was to determine the effect of the jigsaw method on history learning outcomes in class XI odd semester students of SMA Negeri 6 Bandar Lampung in the academic year 2022/2023. The method used in this study was the experimental method. The population in this study were all students of class XI SMA Negeri 6 Bandar Lampung which collected 55 students, the sample consisted of two classes, namely class XIPS 3 and XIPS 5, where class XI IPS 3 as the experimental class which collected 30 students and class XI IPS 5 as the control class which collected 25 students. Sampling technique using cluster random sampling technique. The instrument in this study used multiple choice tests and hypothesis testing in this study using formula_hit. obtained tdaf = 2.00. So that thit > tdaf means that the hypothesis Ho is rejected, meaning that Ha is accepted. So, the key is that there is an effect of the jigsaw learning model on learning outcomes in class XI odd semester students of SMA Negeri 6 Bandar Lampung for the academic year 2022/2023. In addition, the average history of students who were taught using the jigsaw learning model was higher (64.90) compared to students who were taught using conventional learning methods (54.75).